2015
DOI: 10.4238/2015.november.13.1
|View full text |Cite
|
Sign up to set email alerts
|

Screening potential SSR markers of the anadromous fish Coilia nasus by de novo transcriptome analysis using Illumina sequencing

Abstract: ABSTRACT. RNA-Seq technology has been widely applied to transcriptomics, genomics, molecular marker development, and functional gene studies. In the genome, microsatellites are simple sequence repeats (SSR) with a high degree of polymorphism that are used as DNA markers in many molecular genetic studies. Using traditional methods such as magnetic bead enrichment, only a few microsatellite markers have been isolated. Coilia nasus is an anadromous, small-to-moderately sized fish species that is famous as an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In this study, we identified 40,027 microsatellite markers from the transcriptome dataset. Similar to other fish species, the high proportion of identified microsatellite DNA markers (41.29%) were mononucleotide repeats [ 40 , 93 95 ].…”
Section: Discussionmentioning
confidence: 68%
“…In this study, we identified 40,027 microsatellite markers from the transcriptome dataset. Similar to other fish species, the high proportion of identified microsatellite DNA markers (41.29%) were mononucleotide repeats [ 40 , 93 95 ].…”
Section: Discussionmentioning
confidence: 68%
“…Transcriptome studies can holistically elucidate the functions and structures of genes and the molecular mechanisms of biological processes. The transcriptome is widely used to study the following: cold adaptation and thermal response of polar ectothermic species [5]; genetic diversity [6] and genetic management of commercially important fish [7]; genetic network regulating low-temperature tolerance in fish [8]; high-altitude adaptation [9] and the skeletal muscle of swimming fish [10]; adaptive responses to hypoxia [11], pathogenesis of diseases, and functions of the immune system in fish [12]; and sexual plasticity in sex-changing fish [13].…”
Section: Open Accessmentioning
confidence: 99%
“…RNA-Seq technology has been effectively applied to develop molecular markers in fish [6]. High-quality transcriptomes and a large set of gene-linked SNPs would facilitate functional and population genomic studies in endangered species [56].…”
Section: Single Nucleotide Polymorphisms and Simple Sequence Repeatsmentioning
confidence: 99%
“…In fact, high-throughput sequencing for developing SSR does not require sequencing depth as high as genome assembly and annotation, so the cost of this method is relatively low. Recently, high-throughput sequencing has been used to develop microsatellite markers in many fish, such as Ctenopharyngodon idella (Valenciennes, 1844) (see Yu et al 2014), Coilia nasus Temminck et Schlegel, 1846 (see Fang et al 2015), Colossoma macropomum (Cuvier, 1816) (see Ariede et al 2018), Genypterus chilensis (Guichenot, 1848) (see González et al 2019), and Capoeta aculeata (Valenciennes, 1844) (see Gandomkar et al 2021).…”
Section: Introductionmentioning
confidence: 99%